Influence of a HTR2B Stop Codon on Glucagon Homeostasis and Glucose Excursion in Non-Diabetic Men - Tikkanen, R.; Saukkonen, T.; Fex, M.; Bennet, H.; Rautiainen, M.-R.; Paunio, T.; Koskinen, M.; Panarsky, R.; Bevilacqua, L.; Sjöberg, R. L.; Tiihonen, J.; Virkkunen, M. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Limited data are available about the role of the serotonin 2B (5-HT2B) receptor in the function of human islets. This study aimed to test whether the 5-HT2B receptor contributes to glucose, insulin, and glucagon homeostasis in humans, utilizing a hereditary loss-of-function gene mutation in the receptor, which causes a 50% reduction in the production of the receptor protein in heterozygotes. This clinical study enrolled participants recruited by newspaper advertisements and from mental status examinations. A cohort of participants from a young Finnish founder population composed of 68 non-diabetic males with a mean age of 30 was divided into groups for comparison based on being a 5-HT2B receptor loss-of-function gene mutation (HTR2B Q20*) heterozygote carrier (n=11) or not (n=57). Serum levels of glucose, insulin, and glucagon were measured in a 5 h oral glucose tolerance test using a 75 g glucose challenge. Insulin resistance, insulin sensitivity, and beta cell activity were calculated using the homeostasis model assessment (HOMA2) and whole body insulin sensitivity index (WBISI), as well as the ratio of glucagon to insulin was noted. The areas under the curves (AUCs) were also determined. Concentrations of the serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA) were measured in cerebrospinal fluid (CSF). Covariate adjusted mean score comparisons were applied. Lower glucagon secretion and decreased glucose excursion were observed among HTR2B Q20* carriers as compared with individuals who were homozygotes for the wild-type Q20 allele (controls). No differences in insulin secretion, beta cell activity, insulin resistance, or insulin sensitivity were observed. The glucagon to insulin ratio differed between the HTR2B Q20* carriers and controls. CSF levels of 5-HIAA were similar between groups. Our findings indicate that the 5-HT2B receptor may contribute to the regulation of human glucagon and glucose homeostasis and the interplay between glucagon and insulin secretion.
Keywords: glucose; glucagon; serotonin 2B receptor; oral glucose tolerance test; insulin resistance; BMI